Sustainability-oriented intrinsic motivation for sustainable entrepreneurial venturing: The curvilinear effects of basic psychological needs - Cong Doanh Duong (Current Research in Ecological and Social Psychology)
Sustainability-oriented entrepreneurship plays a crucial role in addressing environmental and social challenges. However, limited research has explored how intrinsic motivation for sustainable entrepreneurship is developed. This study builds on self-determination theory by examining how psychological competence, psychological autonomy, and psychological relatedness influence sustainability-oriented intrinsic motivation and sustainability-oriented entrepreneurial intention. Using data collected from 385 higher education students in Vietnam through a stratified sampling approach, the findings reveal that psychological competence, psychological autonomy, and psychological relatedness independently and positively impact sustainability-oriented intrinsic motivation, which mediates their effects on sustainability-oriented entrepreneurial intention. Negative interactions between psychological competence and psychological autonomy, and between psychological autonomy and psychological relatedness, suggest that fulfilling one need can compensate for the lower fulfillment of the other. However, the interaction between psychological competence and psychological relatedness is non-significant. Additionally, greater alignment between psychological needs enhances intrinsic motivation, while significant imbalances, particularly between psychological autonomy and psychological relatedness or psychological competence and psychological relatedness, reduce it. These findings provide practical insights for fostering sustainability-oriented entrepreneurial behaviors by addressing the balanced satisfaction of psychological needs.